Simultaneous adsorption of methyl red and methylene blue onto biochar and an equilibrium modeling at high concentration. (November 2016) - Ding, Guanyu; Wang, Buyun; Chen, Lingyu; Zhao, Shuangjiao
Abstract: Methyl red, methylene blue and biochar were used to investigate simultaneous adsorption of dyes onto low-cost adsorbent at different concentrations combinations. Langmuir mixed model could describe the adsorption well at low concentrations. However, it could not describe the adsorption anymore when concentrations of methyl red and methylene blue were higher than 255 and 300 mg L −1 respectively with 0.5 g L −1 biochar loading. A new model on the interaction among adsorbed adsorbates at equilibrium was developed. It could describe the adsorption at high concentrations well. According to the experimental results, interaction among dyes molecules would replace the competition onto adsorbent to be the main factor influencing adsorption when amount of adsorbed adsorbates were higher than those required to form a monolayer on all the adsorbing sites of adsorbent. The model was further verified by adsorption with other solute such as glucose or NaCl in solution. Highlights: A multi-component isotherm model was built. The model was verified by methyl red and methylene blue adsorption onto biochar. Validity of the model was explored. Adsorption also met with the model well with more solutes. Parameter n in this model could describe the relationship among adsorbates.